FEA based discrete-time sliding mode control of uncertain continuum mechanics MIMO vibrational systems. (10th November 2019) - Homaeinezhad, M.R.; Yaqubi, S.; Fotoohinia, F.
Abstract: In this paper, a novel method for control of uncertain MIMO flexible systems is proposed. The control system is constructed such that it is capable of stabilizing a flexible dynamical system based on rigid approximation of continuum dynamics, resulting in facilitation of modeling and control procedures for complicated vibrational systems. In order to ensure system stability in real-time applications, the control system is obtained in discrete-time basis. To these ends, a sliding hyper-plane based sliding mode control (SMC) algorithm is constructed featuring sliding functions for individual subsystems. An approximated dummy model of the real system is used alongside the dynamical system in order to estimate parametric and unstructured uncertainties which are evaluated through comparisons between the dummy model, data obtained from the real system and corresponding mathematical model. Conventional SMC techniques introduce undesired effects of chattering which result in amplifying vibrations in flexible systems. To address this issue, an alternate algorithm based on selection of control signals within appropriate bounds is used in order to eliminate chattering and provide superior performance in comparison with conventional SMC techniques. The accuracy of proposed method has been verified through ANSYS® mechanical APDL-based simulations and its effectiveness has been verified in multiple operating conditions. Highlights: Constructing precise stable sliding mode control for uncertain flexible systems incorporating modelling uncertainties. Verification of control structure using ANSYS® finite-element analysis for complicated vibrational dynamics. Construction of SMC algorithm in discrete-time basis such that the feasibility of control in real-time applications is guaranteed. Providing bounded control signals without introducing undesired chattering affects so as not to activate high-frequency vibrations. Investigation of parametric and unstructured uncertainties within ANSYS® mechanical APDL framework.